Comparative Study on Profitability of Sorghum-Legumes Intercropping Systems in Ethiopia - Deressa, Dessalegn Ayana (Research on World Agricultural Economy, 2021)
The imbalance between the crop production and population growth is currently the major issue in Ethiopia. To feed the growing population, increasing the production of food through growing more crop types in the same field as an intercropping is the right strategy. The study was aimed at evaluating the profitability of sorghum-legume intercropping on yield of sorghum. Intercropping sorghum with legumes crops increases the land productivity as its Land Equivalent Ratio is greater than one. In these cases, the land equivalent ratio is greater than one indicating the benefits of intercropping.  In general, legume crops contributed to the yield of sorghum either intercropped with legume or grown up using residual contribution of legumes after a year. Therefore, for maximum sorghum production, farmers should plant either as intercrop or after residual effect of legumes crops. In addition to agronomic parameters used to compare the advantages of any cropping system in small scale farming conditions, total gross monetary value is also used to evaluate economic advantages of intercropping system. ER